OP0310 Pregnancy outcome in women with systemic lupus erythematosus, a multicenter cohort-study. (15th June 2017) - Blomjous, B; Abheiden, C; Kroese, S; Laar, J van; Derksen, R; Bultink, I; Voskuyl, A; Lely, A; Boer, M de; Vries, J de; Fritsch-Stork, R
Abstract : Background: Systemic lupus erythematosus (SLE) predominantly affects women during their fertile period. During pregnancy SLE patients are prone to pregnancy complications and may experience increased disease activity. Objectives: To investigate disease activity around/during pregnancy and pregnancy complications in a European cohort according to antiphospholipid antibody (aPL) status. Additionally data on lifetime pregnancy outcomes and comparison of first and consecutive pregnancies were analyzed. Methods: All ongoing pregnancies of >16 weeks gestation of SLE patients (according to the ACR revised criteria) receiving joint care from rheumatologists and gynecologists in two tertiary centers in the Netherlands between 2000–2015 were included. Disease activity (using SELENA-SLE(P)DAI around and during pregnancy), flare rate according to the SELENA- SLEDAI definitions and pregnancy complications were assessed by medical chart review. Results: From 96 women (84% Caucasian) 144 pregnancies were included. Before (<6 months), during and after pregnancy (<6 months) the median SELENA-SLE(P)DAI score was 2 and mild/moderate flare rates were 6.3%, 18.8% and 13.9% respectively. Three patients developed a severe flare during pregnancy, 2 patients postpartum; all were aPL negative. Severe maternal complications (preeclampsia, eclampsia or HELLP-syndrome) occurred in 16.2% of aPL negative, 21.4% of aPL positive SLE patients, and in 30.8% of SLE patients with antiphospholipid syndrome (APS) (GEE; no significant differences between groups). HELLP-syndrome occurred in 23.1% of SLE patients with APS and in 3.1% of SLE patients without APS (Chi-Square; p<0.01). The perinatal complications intrauterine fetal death, preterm birth, small-for-gestational age and neonatal lupus occurred in 4.1%, 32.7%, 14.8%, 1.4%, respectively (GEE; no significant differences between groups). Maternal and perinatal complication rates were similar in first (18.5% and 41.4%) and consecutive (17.6% and 35.1%) pregnancies (Chi-Square; p=0.88 and p=0.44). Of all patients, 42.7% developed a complication during all of their pregnancies (obstetrical history included). Conclusions: This is the first study in patients with SLE demonstrating that incidence rates of pregnancy complications do not decrease in consecutive pregnancies compared to first pregnancies, in contrast to findings in the general population. Except for HELLP-syndrome, pregnancy complications were not significant different between aPL groups. Despite overall low disease activity and the absence of aPL in the majority of patients, almost half of the patients developed a complication during their pregnancies. Disclosure of Interest: B. Blomjous: None declared, C. Abheiden: None declared, S. Kroese: None declared, J. van Laar Grant/research support from: MSD, Pfizer, Roche, Eli Lilly, BMS and Crescendo, R. Derksen: None declared, I. Bultink: None declared, A. Voskuyl: None declared, A. Lely: None declared, M. de Boer: None declared, J. de Vries Grant/research support from: Pfizer, R. Fritsch-Stork: None declared